2019
DOI: 10.3390/electronics8070792
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Sulfidation Behavior on Palladium-Coated Copper Wire with a Flash-Gold Layer (PCA) after Wire Bonding

Abstract: Palladium-coated copper wire with a flash-gold layer (PCA) is an oxidation-resistant fine wire that simultaneously has the properties of palladium-coated copper wire (PCC) and gold-coated copper wire. This research used an extreme sulfidation test to compare corrosion resistance between the PCC and PCA wires. In addition to closely examining the morphology of the wires, the internal matrix after the sulfidation test is also discussed. In doing so, the PCA wire was bonded onto the aluminum pads and the sulfidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…PCC wire generally presents a much larger stitch bond window and more robust second bond, and shows better performance on Al pads in humidity stress and oxidation environments compared with bare Cu wire. It gains market share very fast as it can reduce chloride corrosion risk and resolve the limitation of bare Cu wire, especially on oxidation issues [ 96 , 97 ].…”
Section: Cu Bonding Wirementioning
confidence: 99%
“…PCC wire generally presents a much larger stitch bond window and more robust second bond, and shows better performance on Al pads in humidity stress and oxidation environments compared with bare Cu wire. It gains market share very fast as it can reduce chloride corrosion risk and resolve the limitation of bare Cu wire, especially on oxidation issues [ 96 , 97 ].…”
Section: Cu Bonding Wirementioning
confidence: 99%
“…A comparison has also been made between the reliability of PCC wire bonding and Au wire bonding, revealing longer failure times for PCC wire bonding and slower growth of IMCs. Kuan-Jen Chen et al [ 54 ] conducted extreme sulfurization tests to compare the corrosion resistance of PAC (Palladium-coated Cu wire with a flash-gold layer, which combines the characteristics of PCC and gold-plated Cu wire) and PCC. Both types of Cu wire were wire bonded to Al pads, and it was found that the gold-plated layer of the PAC wire effectively enhanced its resistance to sulfurization corrosion.…”
Section: Bonding Reliabilitymentioning
confidence: 99%
“…Wire bonding is the most widely used technology in the electronic packaging industry [ 1 , 2 , 3 ]. Previously, gold wire was the most commonly used material in wire bonding, but with the high price of gold, many alternative materials have been proposed [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%